Educação ambiental e agrotóxicos: um estudo a partir do projeto político e da prática pedagógica de escolas estaduais ensino fundamental II, do município de Pato Branco - PR - Mezomo, Iara Lucia Tecchio (2024)
The objective of this dissertation was to investigate how environmental education (EA) is included in the Political Pedagogical Project (PPP) of two State Schools in the city of Pato Branco-PR, and how the theme of pesticides is linked to EA in the ninth year of teaching. Fundamental (EF). To this end, the instructions from the State Department of Education of the State of Paraná that deal with EA were analyzed, highlighting: State Law of Paraná (N.17.505/2013); Paraná State Environmental Education Program (PEEA-PR); Curricular Guidelines of Paraná and Curricular Reference of Paraná. The research site was two state schools, one located in the urban area - Colégio Estadual Professor Agostinho Pereira and the other located in the rural area - Colégio Estadual do Campo São Roque. Both schools serve students from the countryside, who frequently come into contact with pesticides. And the participants were six teachers from each school who teach the ninth year of PE. For data collection, a semi-structured interview was applied. The data obtained was analyzed using the Content Analysis technique proposed by Bardin. As for document analysis, the results reveal that EA is not just an isolated discipline, but a comprehensive educational approach that must be integrated into all disciplines, and must be applied in a transversal, interdisciplinary and transdisciplinary way in the curricular components of each discipline. The interviews revealed that, in general, the practices adopted by teachers reflect a conservative approach. These practices include behaviors aimed at preserving the environment, transmitting information and promoting awareness about environmental issues. These characteristics are aligned with the guidelines provided by the Paraná State Department of Education. Regarding the topic of pesticides, it is not included in the schools' PPP and is still little discussed in the classroom. Teachers highlighted the insufficiency of the approach to pesticides in the content of the ninth year of EF. This can be a significant limitation, as students may not receive adequate information about the impacts of pesticides on society and the environment.